2020
DOI: 10.1097/corr.0000000000001305
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Skeletal Oncology Research Group Algorithm’s Prediction of 5-year Survival in Patients with Chondrosarcoma Perform on International Validation?

Abstract: Background The Skeletal Oncology Research Group (SORG) machine learning algorithm for predicting survival in patients with chondrosarcoma was developed using data from the Surveillance, Epidemiology, and End Results (SEER) registry. This algorithm was externally validated on a dataset of patients from the United States in an earlier study, where it demonstrated generally good performance but overestimated 5-year survival. In addition, this algorithm has not yet been validated in patients outside th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…The results from the present study are supported by a few other studies: a retrospective study including 41 patients indicated survival advantage for 16 patients treated with ifosfamide-based chemotherapy [17], another study reported activity and benefit of doxorubicin in 34 patients with advanced DDCS [18] and a third study on 18 patients with DDCS arising in osteochondromas showed beneficial survival for patients treated with a combination regimen as in the present study [19]. A recent report comparing patients with chondrosarcoma from the SEER database with patients treated at an Italian reference centre found that in the subgroup of patients with DDCS, the 5-year OS was higher (37% versus 21%) for Italian patients [20], although there were no differences in baseline characteristics between the groups. The reason for the higher survival was attributed to the difference in the use of chemotherapy in patients with localised DDCS.…”
Section: Discussionsupporting
confidence: 62%
“…The results from the present study are supported by a few other studies: a retrospective study including 41 patients indicated survival advantage for 16 patients treated with ifosfamide-based chemotherapy [17], another study reported activity and benefit of doxorubicin in 34 patients with advanced DDCS [18] and a third study on 18 patients with DDCS arising in osteochondromas showed beneficial survival for patients treated with a combination regimen as in the present study [19]. A recent report comparing patients with chondrosarcoma from the SEER database with patients treated at an Italian reference centre found that in the subgroup of patients with DDCS, the 5-year OS was higher (37% versus 21%) for Italian patients [20], although there were no differences in baseline characteristics between the groups. The reason for the higher survival was attributed to the difference in the use of chemotherapy in patients with localised DDCS.…”
Section: Discussionsupporting
confidence: 62%
“…A logistic regression model for predicting whether Af would recur within a year was created using 70% of the data as a training set and the remaining data to validate the accuracy. The efficiency of the model was evaluated by concordance index (C-index), and the discriminant performance of the model was measured using C-statistic, ranging from 0.5 (random forecast) to 1.0 (excellent distinction) (17). In the calibration plot, calibration could be envisioned.…”
Section: Discussionmentioning
confidence: 99%
“…The "None" line would display the expected net benefit if the interference changes were not performed. The "ALL" line presents the expected net benefit of developing the intervention for all patients (17).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, we formulated a nomogram. The efficiency of the nomogram was judged by concordance index (C-index), and the discriminant performance of the model was measured using Cstatistics, which varies from 0.5 (random forecast) to 1.0 (excellent distinction) (20). In the calibration plot, calibration could be envisioned.…”
Section: Discussionmentioning
confidence: 99%
“…The "None" line would show the expected net benefit if the interference changes were not performed. The "ALL" line presents the expected net benefit for all patients with the intervention development (20).…”
Section: Discussionmentioning
confidence: 99%